KEAMANAN SIBER DALAM PERBANKAN SERTA TANTANGAN DAN SOLUSI DI ERA DIGITAL - Febriantika Nur Afifah, Eka; Widya Evriyanti Simatangkir, Diny; Salsabila Faliha, Nafiza (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The development of digital technology has brought about a major transformation in the banking industry, making services faster, more efficient and accessible. However, these advancements also present major challenges in the form of evolving cybersecurity threats. This research discusses the level of cyber threats faced by the banking sector, the main challenges in implementing an effective cybersecurity system, and innovative solutions to strengthen digital defences. Using a qualitative approach through literature review, this research identifies threats such as malware, phishing, ransomware, and DDoS attacks, and examines best practices in dealing with these risks. In addition, the proposed solutions include implementing the latest technologies such as artificial intelligence and blockchain, strengthening regulations, and increasing awareness and education for employees and customers. The results of this research are expected to contribute to the development of effective cybersecurity strategies to protect data, maintain customer trust, and ensure the operational stability of the banking sector in the digital era.